Embracing “G-D’s Physics” as the New Twenty-First Century Valid Scientific Paradigm! - Bentovish, Jehonathan (European Journal of Applied Sciences, 2023)
Twenty-First Century Theoretical Physics is undergoing a major “Paradigmatic-Shift” from the Old “Material-Causal” Paradigm of (20th century’s) General Relativity Theory (GRT) and Quantum Mechanics (QM) to the New “G-D’s Physics” (“Computational Unified Field Theory”, CUFT) based on a “G-D’s Physics” proven capacity to resolve the “theoretical inconsistency” between GRT & QM and offer an alternative satisfactory explanation for the accelerated rate of the universe’s expansion. Specifically, the empirical validations of “G-D’s Physics;” two unique “Critical Predictions” regarding the “Universe’s Non-Continuous Increase in its Accelerated Rate of Expansion” (UNCIARE) and “Proton-Radius Puzzle” associated findings, as “more valid” than the corresponding predictions of GRT & QM establish “G-D’s Physics as the New Scientific Paradigm for 21st century Theoretical Physics! It is also shown to completely unify between GRT & QM based on the discovery of a singular higher-ordered “Universal Computational Principle” (UCP) that simultaneously computes all exhaustive spatial pixels in the universe at the incredible rate of “c2/h” = 1.36-50 sec’! leading to the discovery of a “Universal Computational Formula” (UCF) that unifies (for the first time in Physics) between the four basic physical features of “space”, “energy”, “mass” and “time”. Finally, the profound theoretical postulates of “G-D’s Physics” New Scientific Paradigm also point at this UCP’s “pre-planning” and “steering” of the entire physical universe towards an “Ultimate Perfected Geulah Goal State” of the universe in which Humanity (and Science) will recognize the singularity of this UCP and live according to its primary characteristics of “All-Goodness”, ”Morality”, “Peace” and “Harmony”, e.g., which is signified by Science’s “embracing” of “G-D’s Physics” as the New 21st Century Scientific Paradigm!